Sustainable Leadership: Mobilizing Islamic Social Finance for Digital Transformation in the 4.0 Education Era - Badrudin Udin; Hanim Misbah (CV. Bimbingan Belajar Assyfa, 2025)
The Industrial Revolution 4.0 era demands that educational institutions undertake massive digital transformation, but budget constraints are often a major obstacle to its implementation. This research is driven by the need for a sustainable leadership model capable of integrating Islamic social finance instruments as an alternative funding solution. The primary objective of this study is to analyze sustainable leadership strategies in mobilizing zakat, infaq, sedekah, and waqf (ZISWAF) funds to support infrastructure digitalization and improve human resource competency in the education sector. Using descriptive qualitative methods through literature review and document analysis, this study examines various models of social finance governance that are adaptive to changing times. The results show that sustainable leadership focuses not only on operational efficiency but also on creating an inclusive digital ecosystem through the strategic and transparent use of Islamic social funds. These findings indicate that the synergy between Islamic leadership values ​​and the potential of social finance can accelerate the development of educational technology without relying solely on government assistance or high operational costs. In conclusion, the mobilization of Islamic social finance under sustainable leadership is key to ensuring the sustainability of digital transformation in educational institutions in the 4.0 era. The implications of this research emphasize the importance of strengthening digital financial literacy for institutional leaders to optimize the potential of Islamic philanthropy.